Susceptibility of Pathogenic Actinomycetes to Antimicrobial Compounds - Lerner, Phillip I. (1974)
Current interest in antimicrobial susceptibility testing of anaerobic pathogens and recent recognition that actinomycetes other than Actinomyces israelii may cause actinomycosis in man prompted this in vitro survey of 74 strains of actinomycetes, representing seven species. Minimum inhibitory concentrations (MICs) for 24 antimicrobials were determined by inhibition of gross colonial enlargement in semisolid antibiotic agar after incubation at 37 C for 48 h under anaerobic conditions. Erythromycin and rifampin were the most active drugs in vitro (MICs of 0.008 to 0.25 μg/ml), although a small number of non-israelii strains were conspicuously more resistant to the latter (MICs >0.5 μg/ml). Penicillin G, cephaloridine, minocycline, and clindamycin were also very active in vitro (MICs of 0.03 to 1.0 μg/ml); for a few non-israelii strains the MICs of clindamycin were 2.0 to 8.0 μg/ml. MICs of cephalothin, ampicillin, lincomycin, tetracycline, doxycycline, and chloramphenicol were well within a therapeutic range for all strains of A. israelii and most other species, although the MIC of lincomycin against a few non-israelii strains and of tetracycline and doxycycline against the majority of these strains was 2.0 to 8.0 μg/ml. Oxacillin, dicloxacillin, and cephalexin were less active in vitro, particularly against strains other than A. israelii. Most non-israelii species were not suppressed by 125 μg of metronidazole per ml, which concentration inhibited all strains of A. israelii; otherwise, there were no antimicrobial susceptibility differences among the species tested. Aminoglycoside activity was negligible.